Mind, Behaviour and Health: A Randomised Experiment - Yonas Alem; Hannah Behrendt; Michèle Belot; Anikó Bíró (Institute for the Study of Labor (IZA), 2016)
Behavioural attitudes towards risk and time, as well as behavioural biases such as present bias, are thought to be important drivers of unhealthy lifestyle choices. This paper makes the first attempt to explore the possibility of training the mind to alter these attitudes and biases, and health-related behaviours in particular, using a randomized controlled experiment. The training technique we consider is a well-known psychological technique called "mindfulness", which is believed to improve self-control and reduce stress. We conduct the experiment with 139 participants, half of whom receive a four-week mindfulness training, while the other half are asked to watch a four-week series of historical documentaries. We evaluate the impact of our interventions on risk-taking and inter-temporal decisions, as well as on a range of measures of health-related behaviours. We find evidence that mindfulness training reduces perceived stress, but only weak evidence on its impact on behavioural traits and health-related behaviours. Our findings have significant implications for a new domain of research on training the mind to alter behavioural traits and biases that play important roles in lifestyle.
Keywords: C81; C91; D81; I10; I12; 330; health-related behaviours; behavioural traits; present bias; stress; experiment